\((x-3y)-xdy/dx=0\)

\(-dy/dx-((x-3y)/x)=0\)

\(dy/dx-x/x+3y/x=0\)

\(dy/dx+3/x y=1\)

\(dy/dx+Py=Q\)

where \(P=3/x\), Q=1

\(I.F.= e^(int Pdx)\)

\(= e^(int 3/x dx)\)

\(= e^(3ln abs(x))\)

\(= e^(ln(x)^3)\)

\(= x^3\)

\(y(I.F.)= int Q(I.F.)+C\)

\(y(x^3)= int 1(x^3)+C\)

\(= x^4/4+C\)

\(y= x/4+C/x^3\)

\(= x/4+C_1\)

\(C_1= C/x^3\)

\(-dy/dx-((x-3y)/x)=0\)

\(dy/dx-x/x+3y/x=0\)

\(dy/dx+3/x y=1\)

\(dy/dx+Py=Q\)

where \(P=3/x\), Q=1

\(I.F.= e^(int Pdx)\)

\(= e^(int 3/x dx)\)

\(= e^(3ln abs(x))\)

\(= e^(ln(x)^3)\)

\(= x^3\)

\(y(I.F.)= int Q(I.F.)+C\)

\(y(x^3)= int 1(x^3)+C\)

\(= x^4/4+C\)

\(y= x/4+C/x^3\)

\(= x/4+C_1\)

\(C_1= C/x^3\)